1995
DOI: 10.1002/1097-0142(19950101)75:1+<203::aid-cncr2820751308>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Bone cancers

Abstract: Background. Frequency distribution data for primary bone sarcomas have long been used to provide clues to the diagnosis of bone cancers after their identification in radiographs. Age and skeletal site are often helpful, in addition to specific radiographic features, in narrowing down the probable histologic categories of bone neoplasms before biopsy. Methods. Data on 2627 histologically confirmed primary malignant tumors of bone, as collected by the SEER program during the period 1973‐1987, were analyzed by ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
385
1
4

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 545 publications
(402 citation statements)
references
References 19 publications
12
385
1
4
Order By: Relevance
“…It was originally reported that males were affected with osteosarcoma more frequently than females 1, 15, 16, 17. However, recent reports suggested that the osteosarcoma incidence may be equal in both sexes 18, 19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was originally reported that males were affected with osteosarcoma more frequently than females 1, 15, 16, 17. However, recent reports suggested that the osteosarcoma incidence may be equal in both sexes 18, 19.…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma, the most common primary malignancy of bone, typically occurs among children and adolescence 1. For young patients, it can occur in any bone with the major sites in long bone, especially in the distal femur, proximal tibia, and proximal humerus 2, 3.…”
Section: Introductionmentioning
confidence: 99%
“…The overall 5-year survival rate is 41.2%. 1,2 Moreover, the prognosis is poor for patients who have had a relapse and for patients with large primary tumors or metastatic disease at presentation. Therefore, new strategies are needed to improve the survival rates.…”
mentioning
confidence: 99%
“…Primary angiosarcoma of bone is extremely rare and accounts for less than 1% of all angiosarcomas [2,5,7,15]. Dorfman and Czerniak [4] reported only 36 (1.4%) of 2627 primary bone sarcomas were classified as angiosarcomas. These tumors usually occur in long tubular bones and much less frequently in the ribs, pelvis, and vertebrae.…”
Section: Discussion and Treatmentmentioning
confidence: 99%